LATE SKIN REACTIONS ASSOCIATED WITH THE MODERN VACCINE - Machado, Verónica Arango; Triana, César Camilo León; Cordero, Jhon Fredy Bello; Vásquez, Ángela María Saibis; Rodríguez, Presleys Márquez; Álvarez, Edmundo Alberto Molina; Ossa, María José Durango de la; Esteves, Edwar Enrique Peña (Jour Med Resh and Health Sci, 2021)
The infection by the SARS-CoV-2 virus and the disease generated by COVID-19 that began in 2019 in Wuhan China has had a great impact on global morbidity and mortality, which in turn led to the creation in record time of the first vaccines used in humans against coronavirus. Vaccines such as Sinovac, Janssen, AstraZeneca, Pfizer and Moderna, of which have been authorized and administered in multiple countries with really favorable results. However, late post-vaccination adverse effects have been reported in patients vaccinated especially by Moderna and Pfizer, observing a compromise at the level of the skin causing the appearance in most cases of urticaria, edema, erythema, reactivation of herpes zoster, morbilliform eruptions, among others that are undoubtedly related to the mechanisms of action of the aforementioned vaccines.